Evaluation of Cascading and Alignment of Management Key Performance Indicators - Putri, Yolanda; Hermawan, Ancella Anitawati (E-Jurnal Akuntansi, 2025)
This study evaluates the cascading and alignment processes of Key Performance Indicators (KPIs) at PT XYZ. The central issue identified is the misalignment between KPI performance scores at the business unit level and those at the Director and Corporate levels. The research employs a combination of primary data obtained through interviews and secondary data drawn from organizational documents. A triangulation method—comprising document analysis, interviews, and strategy map evaluations—is used to assess KPI alignment across the Corporate, Director, and business unit levels. The findings indicate that, overall, KPIs have been effectively cascaded, with clear causal linkages observed between strategic objectives across organizational levels. However, a notable misalignment was identified in Business Unit 3, primarily due to a limited understanding of the cascading process. This study contributes to the literature by offering practical recommendations to enhance KPI alignment, including improved inter-unit coordination, the integration of technology-based monitoring systems, and strengthened organizational understanding of the KPI cascading framework. These measures are essential to support the effective realization of the company’s strategic vision. Keywords: Alignment; Balance Scorecard; Cascading; Key Performance Indicators; Strategy Maps